Novel Anti-amoebic Properties of Agarophytes Gracilaria changii and Gracilaria salicornia Extracts - Goh, Tiong Keat *; Yow, Yoon Yen *; Ayaz, Anwar *; Khan, Naveed Ahmed *; Ong, Seng Kai * (Bentham Science Publishers, 2023)
Introduction: Acanthamoeba is a ubiquitous and parasitic protozoan capable of causing serious human infections, resulting in blindness and even death. Seaweeds are abundant and widely known for their antimicrobial properties. This study aims to unveil the anti-amoebic potential of two Malaysian red seaweeds, Gracilaria changii and Gracilaria salicornia on Acanthamoeba castellanii.